2017
DOI: 10.1017/s001675681700005x
|View full text |Cite
|
Sign up to set email alerts
|

A revised model for the crustal structure of the SW Grenville Province, Ontario, Canada

Abstract: The Grenville Province forms the exhumed remnants of a 1.1 Ga collisional orogeny that telescoped an older continental margin. Terranes with distinct crustal formation ages can be mapped using Nd isotopes, revealing a ramp–flat thrust structure. The ramp is identified by the presence of retrogressed eclogites, and its trajectory is refined using Nd model ages. The main allochthon is locally overlain by the Parry Sound klippe, but is also underlain by a tectonic duplex. Northwest-directed nappes represent remna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 48 publications
1
4
0
Order By: Relevance
“…4; Dickin et al 2014). Figure 4a is a map of the crustal structure of the SW Grenville Province, based on Nd isotope mapping summarized by Dickin et al (2017). This work showed that the surface trajectory of the Allochthon Boundary Thrust is close to the position originally proposed by Rivers et al (1989), along the basal shear zone of the Mesoproterozoic Muskoka domain.…”
Section: Nd Isotope Mappingsupporting
confidence: 54%
See 3 more Smart Citations
“…4; Dickin et al 2014). Figure 4a is a map of the crustal structure of the SW Grenville Province, based on Nd isotope mapping summarized by Dickin et al (2017). This work showed that the surface trajectory of the Allochthon Boundary Thrust is close to the position originally proposed by Rivers et al (1989), along the basal shear zone of the Mesoproterozoic Muskoka domain.…”
Section: Nd Isotope Mappingsupporting
confidence: 54%
“…The location of the ramp is constrained by windows through the allochthon, identified by Nd isotope mapping. The windows and overlying allochthonous domains are exposed as a repetitive antiform-synform pattern perpendicular to the orogen (Dickin et al 2017).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Tectonically driven lateral flow and expulsion of lower crust may have been triggered by underthrusting of a strong indenter. Northwest directed nappes represent remnants of a deep corrugated thrust sheet (e.g., Dickin et al, ; Jamieson & Beaumont, ). They and others interpreted that when tectonic convergence turned off, the orogenic plateau underwent gravitational spreading, in which ductile lower crust flowed laterally from the plateau toward the foreland, driving thrusting on the orogenic flanks and ductile thinning in the orogenic core.…”
Section: The Grenville Orogenymentioning
confidence: 99%